2013
DOI: 10.1371/journal.pone.0055843
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Prevalence of Major Central Nervous System Involvement in Systemic Lupus Erythematosus: A 3-Year Prospective Study of 370 Patients

Abstract: BackgroundThe incidence and prevalence of CNS involvement in SLE remains unclear owing to conflicting results in the published studies. The aim of the study was to evaluate the incidence and prevalence of major definite CNS events in SLE patients.Methods370 SLE patients with no previous history of CNS involvement were prospectively evaluated in a tertiary hospital referral center for 3 years. Major CNS manifestations were codified according to ACR definitions, including chorea, aseptic meningitis, psychosis, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(81 citation statements)
references
References 40 publications
(56 reference statements)
1
74
0
6
Order By: Relevance
“…Epileptic seizures are a common CNS manifestation, occurring in as much as 2-10 % of patients, mainly associated with high disease activity and antiphospholipid antibodies [5,23,28]. Apart from symptomatic antiepileptic therapy, immunosuppression is indicated when high disease activity coexists or whenever there is suspicion of underlying inflammatory m e c ha n i s m s ( g r ad e 3 D ) ; w h e t h er t he p r op o s e d hydroxychloroquine has a protective effect (grade 2C) remains to be determined [23].…”
Section: Acute or Subacute Meningoencephalitis Presenting As Acute Comentioning
confidence: 99%
See 1 more Smart Citation
“…Epileptic seizures are a common CNS manifestation, occurring in as much as 2-10 % of patients, mainly associated with high disease activity and antiphospholipid antibodies [5,23,28]. Apart from symptomatic antiepileptic therapy, immunosuppression is indicated when high disease activity coexists or whenever there is suspicion of underlying inflammatory m e c ha n i s m s ( g r ad e 3 D ) ; w h e t h er t he p r op o s e d hydroxychloroquine has a protective effect (grade 2C) remains to be determined [23].…”
Section: Acute or Subacute Meningoencephalitis Presenting As Acute Comentioning
confidence: 99%
“…The main risk factors are cumulative damage attributed to the systemic disease and antiphospholipid antibodies [5,28], necessitating therapy with anticoagulants or antiplatelet agents (grade 2C), along with adequate control of non-SLE-related risk factors. Dopamine antagonists may be used in persistent chorea (grade 3D) [22,29].…”
Section: Focal Ischemic Manifestationsmentioning
confidence: 99%
“…Neuropsychiatric SLE (NPSLE) refers to several different neurological and/or behavioral clinical syndromes such as stroke, seizures, myelopathy, mood disorders, and cognitive impairment [1] (Table 1), and a 30-40% prevalence rate of NPSLE has recently been reported [2]. In a 3-year prospective study of 370 patients with SLE and no history of CNS complication, 16/370 patients were reported to develop major CNS-related events including myelopathy (4/16), optic neuritis (1/16), and positive neuromyelitis optica (NMO)-IgG antibodies (2/16) [3]. It has been shown that antiphospholipid antibodies including anti-cardiolipin and lupus anti-coagulant are some of the strongest NPSLE-related factors expressed especially in relation to cerebrovascular disease [4,5].…”
Section: Cns Involvement In Slementioning
confidence: 99%
“…As discussed, anti-AQP4 antibodies have been discovered both in patients with NMO and with NPSLE. Table 1: Major manifestations of CNS lupus [3].…”
Section: Neuromyelitis Opticamentioning
confidence: 99%
“…тонико-клонических припадков, у 3 пациентов был эпилептический статус [41]. У 5-10% больных судороги возникают за несколько лет до появления других признаков СКВ [39,42].…”
unclassified